Flame-retardant polyamide composition and preparation method thereof
By adding specific components to the polyamide material and adopting a two-step preparation process, the problems of thermal stability and warping of the polyamide material at high temperatures are solved, and a high-performance polyamide composition is achieved.
Patent Information
- Application Number
- CN202411643403.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyamide materials have poor thermal stability, flammable, easy to absorb moisture and have a large molding shrinkage rate at high temperatures, which cannot meet the high performance needs of industries such as aerospace. At the same time, glass fiber reinforced nylon materials have warping problems.
A polyamide composition is used, which comprises an aliphatic polyamide resin, a metal sulfide, a compatibility agent, a coupling agent, an amorphous semiaromatic polyamide resin, a flat glass fiber and optionally a halogen-free flame retardant Agents, antioxidants and processing aids improve the material's high temperature, friction and low warpage properties through a specific two-step preparation process.
It achieves that the polyamide material has both high temperature resistance, friction resistance and low warping resistance without sacrificing mechanical properties, improving the overall performance of the material.
Smart Images

Figure BDA0005140118600000171 
Figure BDA0005140118600000191 
Figure BDA0005140118600000201
Abstract
Description
Technical Field
[0001] The term polymer material field in this application specifically relates to the field of polymer materials with high temperature resistance, friction resistance and low warping. Background Art
[0002] As an important lightweight thermoplastic, polyamide (nylon) is widely used in aerospace, automobile, instrumentation, home appliances, electronic communications, and new energy fields due to its excellent mechanical properties, wear resistance, and chemical corrosion resistance. In the field of civil aviation, polyamide is mainly used in radomes, landing gears, inner and outer flap compartments, doors, cabin interiors, etc., and has a very wide range of uses.
[0003] However, unmodified polyamide materials have disadvantages such as flammability, easy moisture absorption, poor thermal stability, and large molding shrinkage, which cannot meet the use requirements of the above industries. Therefore, polyamide needs to be modified. In addition, parts such as gears, bearings, gaskets, bushings, and wiring harness jackets may be damaged by friction during long-term use, causing safety hazards.
[0004] Therefore, existing wear-resistant nylon usually needs to be reinforced with glass fiber to improve its wear resistance. However, the anisotropy of glass fiber causes uneven shrinkage of each phase of the product, resulting in obvious product warping.
[0005] On the other hand, when polyamide is modified, molybdenum disulfide metal sulfides are usually added as wear-resistant additives. However, molybdenum disulfide has poor compatibility with the polymer matrix and is unevenly dispersed, which causes the material performance to deteriorate.
[0006] There are many commercial products of glass fiber reinforced polyamide 66, and the performance of products from different manufacturers varies greatly. Generally, foreign manufacturers such as Dupont, BASF, Dow chemical, RTP, etc. provide different grades of products according to actual needs, such as high heat resistance, anti-aging, wear resistance, etc. However, there is currently no polyamide 66 compound that combines high temperature resistance, friction resistance, low warpage and other characteristics.
[0007] Therefore, there is still a need for a polyamide composition that can solve at least one of the problems in the prior art; advantageously, the composition can have the characteristics of high temperature resistance, friction resistance, low warpage, etc. without sacrificing mechanical properties. Summary of the invention
[0008] The purpose of the present application is to provide a polyamide composition having the characteristics of high temperature resistance, friction resistance, low warpage, etc. without sacrificing mechanical properties.
[0009] A first aspect of the present application relates to a polyamide composition comprising:
[0010] a) aliphatic polyamide resin;
[0011] b) Metal sulfides;
[0012] c) compatibilizer;
[0013] d) coupling agent;
[0014] e) an amorphous semi-aromatic polyamide resin;
[0015] f) flat glass fiber;
[0016] Optional g) halogen-free flame retardant;
[0017] Optionally h) an antioxidant;
[0018] Optionally i) processing aids;
[0019] The polyamide composition is prepared by the following method:
[0020] 1) premixing components a) to d) in a high-speed mixer to obtain a first premix;
[0021] 2) feeding the first premix into a twin-screw extruder, and obtaining a second premix as a masterbatch of wear-resistant additive after the steps of melt extrusion, granulation and drying;
[0022] 3) premixing the wear-resistant additive masterbatch with component e), optionally g), optionally h), and optionally i) in a high-speed mixer to obtain a third premix,
[0023] 4) feeding the third premix and component f) flat glass fiber into a twin-screw extruder, and obtaining the polyamide composition after a process including melt extrusion, granulation, and drying, wherein the component f) enters from a side feed port of the twin-screw extruder, and the remaining components enter from a main feed port of the twin-screw extruder.
[0024] The second aspect of the present application relates to a method for preparing the polyamide composition as described in the first aspect, the method comprising:
[0025] 1) Premix the following components a) to d) in a high-speed mixer to obtain a first premix:
[0026] a) aliphatic polyamide resin;
[0027] b) Metal sulfides;
[0028] c) compatibilizer;
[0029] d) coupling agent;
[0030] 2) feeding the first premix into a twin-screw extruder, and obtaining a second premix as a masterbatch of wear-resistant additive after the steps of melt extrusion, granulation and drying;
[0031] 3) Premixing the wear-resistant additive masterbatch with the following components e), optionally g), optionally h), and optionally i) in a high-speed mixer to obtain a third premix:
[0032] e) an amorphous semi-aromatic polyamide resin;
[0033] Optional g) halogen-free flame retardant;
[0034] Optionally h) an antioxidant;
[0035] Optionally i) processing aids;
[0036] 4) feeding the third premix and component f) flat glass fiber into a twin-screw extruder, and obtaining the polyamide composition after a process including melt extrusion, granulation, and drying, wherein the component f) enters from a side feed port of the twin-screw extruder, and the remaining components enter from a main feed port of the twin-screw extruder.
[0037] The third aspect of the present application relates to the following polyamide composition, which comprises:
[0038] a) aliphatic polyamide resin;
[0039] b) Metal sulfides;
[0040] c) compatibilizer;
[0041] d) coupling agent;
[0042] e) an amorphous semi-aromatic polyamide resin;
[0043] f) flat glass fiber;
[0044] Optional g) halogen-free flame retardant;
[0045] Optionally h) an antioxidant;
[0046] Optionally i) processing aids;
[0047] The polyamide composition has the following characteristics:
[0048] -Tensile strength greater than 150MPa,
[0049] - Flexural strength greater than 200MPa,
[0050] -Notched impact strength greater than 13kJ / m 2 ,
[0051] -Tensile strength retention rate greater than 70%;
[0052] - A coefficient of friction of less than 0.10; and
[0053] -Warp height is less than 0.5mm.
[0054] The applicant has unexpectedly discovered that the use of the two-step preparation process according to the present application, together with specific components, makes it possible to obtain a polyamide composition having good mechanical properties, a low friction coefficient and low warpage properties. DETAILED DESCRIPTION
[0055] "Scope" disclosed herein is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be inclusive or exclusive of end values, and can be arbitrarily combined, i.e., any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following range can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In this application, unless otherwise specified, the numerical range "a to b" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0 to 5" means that all real numbers between "0 to 5" are listed in this document, and "0 to 5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0056] In this application, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.
[0057] In this application, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0058] In the present application, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0059] In this application, unless otherwise specified, the terms "include" and "comprising" mentioned herein may be open-ended or closed-ended. For example, the terms "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0060] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number itself, and "several" in "one or several" means two or more.
[0061] In the description herein, unless otherwise specified, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0062] Herein, unless otherwise specified, percentage (%) or part refers to percentage by weight or part by weight relative to the composition.
[0063] Herein, if there is no contrary description, the sum of the contents of the various components in the composition is 100%.
[0064] Herein, if there is no contrary description, the sum of the parts of each component in the composition may be 100 parts by weight.
[0065] In this context, unless otherwise specified, "a combination thereof" means a multi-component mixture of the elements described, for example a mixture of two, three, four and up to the maximum possible multi-component mixture.
[0066] If not specifically stated, the terms "a" or "an" used in the present specification means "at least one".
[0067] Herein, unless otherwise stated, all reactions are carried out at normal temperature and pressure.
[0068] In the context of the present application, the term "polyamide" can be used interchangeably with "polyamide resin", "PA", or "PA resin". For example, the term "aliphatic / semi-aromatic / aromatic polyamide resin" can be used interchangeably with the term "aliphatic / semi-aromatic / aromatic polyamide", "aliphatic / semi-aromatic / aromatic PA", "aliphatic / semi-aromatic / aromatic PA resin".
[0069] In the context of the present application, the expression "two-step process" is to be understood as a production process characterized by the following: in this process, the wear-resistant additive masterbatch is first prepared and then the polyamide composition is prepared.
[0070] In the context of the present application, the expression "one-step process" is understood to mean a production process characterized by the direct production of the polyamide composition without the prior production of a masterbatch of a wear-resistant additive.
[0071] The present application achieves beneficial technical effects in at least one of the following aspects:
[0072] - tensile strength, which can be tested, for example, in ISO 527 standard;
[0073] - Tensile strength retention, which can be tested, for example, by ISO 527 standard;
[0074] - flexural strength, which can be tested, for example, by ISO 178 standard;
[0075] - Flexural strength retention, which can be tested, for example, by ISO 178 standard
[0076] - compressive strength, which can be tested, for example, by ASTM D695-10 standard;
[0077] - compression strength retention, which can be tested, for example, by standard ASTM D695-10;
[0078] - Notched impact strength, which can be tested, for example, by ISO 179 standard;
[0079] - Warp height, which can be measured with a scale;
[0080] - softening point, which can be tested, for example, by standard GB1633-79;
[0081] - Flame retardant properties, which can be tested, for example, by UL94 standard;
[0082] - Sliding friction coefficient, which can be tested, for example, by GB 5763 standard;
[0083] - Aging performance, which can be tested, for example, by standard GB / T7141-2008;
[0084] - Mechanical properties of materials in case of reuse after recycling.
[0085] A first aspect of the present application relates to a polyamide composition, the polyamide composition comprising:
[0086] a) aliphatic polyamide resin;
[0087] b) Metal sulfides;
[0088] c) compatibilizer;
[0089] d) coupling agent;
[0090] e) an amorphous semi-aromatic polyamide resin;
[0091] f) flat glass fiber;
[0092] Optional g) halogen-free flame retardant;
[0093] Optionally h) an antioxidant;
[0094] Optional i) Processing aids
[0095] The polyamide composition is prepared by the following method:
[0096] 1) premixing components a) to d) in a high-speed mixer to obtain a first premix;
[0097] 2) feeding the first premix into a twin-screw extruder, and obtaining a second premix as a masterbatch of wear-resistant additive after the steps of melt extrusion, granulation and drying;
[0098] 3) premixing the wear-resistant additive masterbatch with component e), optionally g), optionally h), and optionally i) in a high-speed mixer to obtain a third premix,
[0099] 4) feeding the third premix and component f) flat glass fiber into a twin-screw extruder, and obtaining the polyamide composition after a process including melt extrusion, granulation, and drying, wherein the component f) enters from a side feed port of the twin-screw extruder, and the remaining components enter from a main feed port of the twin-screw extruder.
[0100] a) Aliphatic polyamide resin
[0101] The polyamide composition of the first aspect of the present application comprises an aliphatic polyamide resin. The nomenclature used to define polyamides is described in ISO Standard 1874-1:2011 Plastics-Polyamide (PA) Moulding And Extrusion Materials-Part 1: Designation and is well known to the skilled person.
[0102] According to one embodiment, the aliphatic polyamide resin of the present application is obtained by the condensation of:
[0103] -C x Aliphatic lactams;
[0104] -C y aliphatic amino acids; or
[0105] -C a Aliphatic diacids and C b Aliphatic diamines.
[0106] According to one embodiment, the C x The aliphatic lactam is selected from C 4 To C 12 Aliphatic lactam, or C 4 To C 10 Aliphatic lactam, or C 4 To C 8 Aliphatic lactams.
[0107] According to one embodiment, the C x Aliphatic lactam is selected from: C 4 Aliphatic lactam, or C 5 Aliphatic lactam, or C 6 Aliphatic lactam, or C 7 Aliphatic lactam, or C 8 Aliphatic lactam, or C 9 Aliphatic lactam, or C 10 Aliphatic lactam, or C 11 Aliphatic lactam, or C 12 Aliphatic lactams.
[0108] As C can be used in this application x As non-limiting examples of aliphatic lactams, there may be mentioned: butyrolactam, valerolactam, caprolactam, enantholactam, capryllactam, nonanolactam, capryllactam, undecanolactam, laurolactam.
[0109] According to one embodiment, the C y The aliphatic amino acids are selected from C 4 To C 12 Aliphatic amino acids, or C 4 To C 10 Aliphatic amino acids, or C 4 To C 8 Aliphatic amino acids.
[0110] According to one embodiment, the C y Aliphatic amino acids are selected from: C 4 Aliphatic amino acids, or C 5 Aliphatic amino acids, or C6 Aliphatic amino acids, or C 7 Aliphatic amino acids, or C 8 Aliphatic amino acids, or C 9 Aliphatic amino acids, or C 10 Aliphatic amino acids, or C 11 Aliphatic amino acids, or C 12 Aliphatic amino acids.
[0111] As C can be used in this application y As non-limiting examples of aliphatic amino acids, there may be mentioned: 4-aminobutyric acid, 5-aminopentanoic acid, 4-aminopentanoic acid, 6-aminohexanoic acid, 5-aminohexanoic acid, 7-aminoheptanoic acid, 6-aminoheptanoic acid, 8-aminooctanoic acid, 7-aminooctanoic acid, 9-aminononanoic acid, 8-aminononanoic acid, 10-aminodecanoic acid, 9-aminodecanoic acid, 11-aminoundecanoic acid, 10-aminoundecanoic acid, 12-aminolauric acid, 11-aminolauric acid.
[0112] According to one embodiment, the C a The aliphatic diacid is selected from: C 4 To C 12 Aliphatic diacid, or C 4 To C 10 Aliphatic diacid, or C 4 To C 8 Aliphatic diacid.
[0113] According to one embodiment, the C a The aliphatic diacid is selected from: C 4 Aliphatic diacid, or C 5 Aliphatic diacid, or C 6 Aliphatic diacid, or C 7 Aliphatic diacid, or C 8 Aliphatic diacid, or C 9 Aliphatic diacid, or C 10 Aliphatic diacid, or C 11 Aliphatic diacid, or C 12 Aliphatic diacid.
[0114] As C can be used in this application a As non-limiting examples of aliphatic diacids, mention may be made of: succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid.
[0115] According to one embodiment, the C b The aliphatic diamine is selected from: C 4 To C 12 Aliphatic diamine, or C 4 To C 10 Aliphatic diamine, or C 4 To C 8Aliphatic diamines.
[0116] According to one embodiment, the C b The aliphatic diamine is selected from: C 4 Aliphatic diamine, or C 5 Aliphatic diamine, or C 6 Aliphatic diamine, or C 7 Aliphatic diamine, or C 8 Aliphatic diamine, or C 9 Aliphatic diamine, or C 10 Aliphatic diamine, or C 11 Aliphatic diamine, or C 12 Aliphatic diamines.
[0117] As C can be used in this application b As non-limiting examples of aliphatic diamines, mention may be made of: 1,4-tetramethylenediamine, 1,5-pentamethylenediamine, 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undemethylenediamine, 1,12-dodecamethylenediamine.
[0118] In the polyamide composition described in the first aspect of the present application, the content of the aliphatic polyamide resin can be adjusted according to the desired properties of the final product.
[0119] According to one embodiment, in the polyamide composition described in the first aspect of the present application, the content of the aliphatic polyamide resin is 10 to 40 weight %, or 10 to 35 weight %, or 10 to 30 weight %, based on the total weight of the polyamide composition.
[0120] For example, in the polyamide composition described in the first aspect of the present application, the content of the aliphatic polyamide resin may be 10 weight%, or 11 weight%, or 12 weight%, or 13 weight%, or 14 weight%, or 15 weight%, or 16 weight%, or 17 weight%, or 18 weight%, or 19 weight%, or 20 weight%, or 21 weight%, or 22 weight%, or 23 weight%, or 24 weight%, or 25 weight%, or 26 weight%, or 27 weight%, or 28 weight%, or 29 weight%, or 30 weight%, or 31 weight%, or 32 weight%, or 33 weight%, or 34 weight%, or 35 weight%, or 36 weight%, or 37 weight%, or 38 weight%, or 39 weight%, or 40 weight%, based on the total weight of the polyamide composition.
[0121] b) Metal sulfides
[0122] The polyamide composition described in the first aspect of the present application contains metal sulfide.
[0123] According to one embodiment, the metal in the metal sulfide is selected from transition metals, Group IV metals, and Group V metals. As a preferred embodiment, the metal in the metal sulfide is selected from tin, bismuth, iron, cobalt, nickel, copper, zinc, molybdenum, and tungsten. As a more preferred embodiment, the metal sulfide is selected from one or more of molybdenum disulfide, tungsten disulfide, and bismuth sulfide.
[0124] In the polyamide composition described in the first aspect of the present application, the content of the metal sulfide can be adjusted according to the desired properties of the final product.
[0125] According to one embodiment, in the polyamide composition described herein, the content of the metal sulfide is 5 to 20 wt%, or 5 to 18 wt%, or 5 to 16 wt%, or 5 to 14 wt%, or 5 to 12 wt%, based on the total weight of the polyamide composition.
[0126] For example, in the polyamide composition described herein, the content of the metal sulfide may be 5 wt%, or 6 wt%, or 7 wt%, or 8 wt%, or 9 wt%, or 10 wt%, or 11 wt%, or 12 wt%, or 13 wt%, or 14 wt%, or 15 wt%, or 16 wt%, or 17 wt%, or 18 wt%, or 19 wt%, or 20 wt%, based on the total weight of the polyamide composition.
[0127] c) Compatibilizer
[0128] The polyamide composition described in the first aspect of the present application comprises a compatibilizer.
[0129] According to one embodiment, the compatibilizer is selected from a copolymer formed by a hydrophilic unit and a hydrophobic unit. Preferably, the compatibilizer is selected from a graft copolymer formed by a hydrophilic compound and a hydrophobic polymer.
[0130] According to one embodiment, in the copolymer formed by the hydrophilic unit and the hydrophobic unit, the hydrophilic unit is a unit derived from acrylic acid, acrylamide, vinyl alcohol, vinyl alcohol ester, vinyl sulfonic acid, p-vinyl benzoic acid, or maleic anhydride.
[0131] According to one embodiment, in the copolymer formed by the hydrophilic unit and the hydrophobic unit, the hydrophobic unit is a unit derived from α-olefin, diene, styrene, or acrylonitrile.
[0132] According to one embodiment, in the graft copolymer formed by the hydrophilic compound and the hydrophobic polymer, the hydrophilic compound is derived from one or more of acrylic acid, acrylamide, vinyl alcohol, vinyl alcohol ester, vinyl sulfonic acid, p-vinyl benzoic acid, or maleic anhydride.
[0133] According to one embodiment, in the graft copolymer formed by the hydrophilic polymer and the hydrophobic polymer, the hydrophobic polymer is formed by one or more of α-olefin, diene, styrene and acrylonitrile.
[0134] As non-limiting examples of the compatibilizer that can be used in the present application, one or more of PP-g-MAH, PE-g-MAH, EVA, ABS-g-MAH can be mentioned.
[0135] In the polyamide composition described in the first aspect of the present application, the content of the compatibilizer can be adjusted according to the desired properties of the final product.
[0136] According to one embodiment, in the polyamide composition described in the first aspect of the present application, the content of the compatibilizer is 1 to 5 weight %, or 1 to 4.5 weight %, or 1 to 4 weight %, or 1 to 3.5 weight %, based on the total weight of the polyamide composition.
[0137] For example, in the polyamide composition described in the first aspect of the present application, the content of the compatibilizer may be 1.0 wt%, or 1.1 wt%, or 1.2 wt%, or 1.3 wt%, or 1.4 wt%, or 1.5 wt%, or 1.6 wt%, or 1.7 wt%, or 1.8 wt%, or 1.9 wt%, or 2.0 wt%, or 2.1 wt%, or 2.2 wt%, or 2.3 wt%, or 2.4 wt%, or 2.5 wt%, or 2.6 wt%, or 2.7 wt%, or 2.8 wt%, or 2.9 wt%. %, or 3.0 wt %, or 3.1 wt %, or 3.2 wt %, or 3.3 wt %, or 3.4 wt %, or 3.5 wt %, or 3.6 wt %, or 3.7 wt %, or 3.8 wt %, or 3.9 wt %, or 4.0 wt %, or 4.1 wt %, or 4.2 wt %, or 4.3 wt %, or 4.4 wt %, or 4.5 wt %, or 4.6 wt %, or 4.7 wt %, or 4.8 wt %, or 4.9 wt %, or 5.0 wt %, based on the total weight of the polyamide composition.
[0138] d) Coupling agent
[0139] The polyamide composition described in the first aspect of the present application comprises a coupling agent.
[0140] According to one embodiment, the coupling agent is selected from: a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.
[0141] As non-limiting examples of the silane coupling agent, there can be mentioned: KH550, KH560, KH570, KH590, KH602, KH172, KH902, KRN8026. It should be understood that those skilled in the art can also use other silane coupling agents according to actual needs.
[0142] As non-limiting examples of the titanate coupling agent, there can be mentioned: RZ-311W, NXH-401, HY-803, HTW-401, TMC-311W. It should be understood that those skilled in the art can also use other titanate coupling agents according to actual needs.
[0143] As non-limiting examples of the aluminate coupling agent, there can be mentioned: JTW-18, isopropyl distearoyloxy aluminate, distearoyloxy phenoxy aluminate, DL411. However, it should be understood that those skilled in the art can also use other aluminate coupling agents according to actual needs.
[0144] In the polyamide composition described in the first aspect of the present application, the content of the coupling agent can be adjusted according to the desired properties of the final product.
[0145] According to one embodiment, in the polyamide composition described in the first aspect of the present application, the content of the coupling agent is 1 to 3 weight %, or 1 to 2.5 weight %, or 1 to 2 weight %, based on the total weight of the polyamide composition.
[0146] For example, in the polyamide composition described in the first aspect of the present application, the content of the coupling agent may be 1.0 wt%, or 1.1 wt%, or 1.2 wt%, or 1.3 wt%, or 1.4 wt%, or 1.5 wt%, or 1.6 wt%, or 1.7 wt%, or 1.8 wt%, or 1.9 wt%, or 2.0 wt%, or 2.1 wt%, or 2.2 wt%, or 2.3 wt%, or 2.4 wt%, or 2.5 wt%, or 2.6 wt%, or 2.7 wt%, or 2.8 wt%, or 2.9 wt%, or 3.0 wt%, based on the total weight of the polyamide composition.
[0147] e) Amorphous semi-aromatic polyamide resin
[0148] The polyamide composition described in the first aspect of the present application comprises an amorphous semi-aromatic polyamide resin.
[0149] According to one embodiment, the amorphous semiaromatic polyamide resin may be selected from PA6I, 11 / B10, 12 / B10, 11 / P10, 12 / P10, 11 / BI / BT, 12 / BI / BT, 11 / PI / BT, 12 / PI / BT, 11 / PI / PT, 12 / PI / PT, 11 / BI, 12 / BI, 11 / PI and 12 / PI.
[0150] In the polyamide composition described in the first aspect of the present application, the content of the amorphous semi-aromatic polyamide resin can be adjusted according to the desired product properties.
[0151] According to one embodiment, in the polyamide composition described in the first aspect of the present application, the content of the amorphous semi-aromatic polyamide resin is 10 to 40 weight %, or 10 to 35 weight %, or 10 to 30 weight %, based on the total weight of the polyamide composition.
[0152] For example, in the polyamide composition described in the first aspect of the present application, the content of the amorphous semi-aromatic polyamide resin may be 10 weight%, or 11 weight%, or 12 weight%, or 13 weight%, or 14 weight%, or 15 weight%, or 16 weight%, or 17 weight%, or 18 weight%, or 19 weight%, or 20 weight%, or 21 weight%, or 22 weight%, or 23 weight%, or 24 weight%, or 25 weight%, or 26 weight%, or 27 weight%, or 28 weight%, or 29 weight%, or 30 weight%, or 31 weight%, or 32 weight%, or 33 weight%, or 34 weight%, or 35 weight%, or 36 weight%, or 37 weight%, or 38 weight%, or 39 weight%, or 40 weight%, based on the total weight of the polyamide composition.
[0153] f) Flat glass fiber
[0154] The polyamide composition described in the first aspect of the present application comprises flat glass fibers.
[0155] In the context of the present application, the terms "glass fiber" and "glass fibers" are used interchangeably.
[0156] In the context of the present application, the term "flat glass fiber" means a glass fiber having the following characteristics: in a cross section perpendicular to the length direction of the glass fiber, there is a longer dimension L and a shorter dimension D.
[0157] According to one embodiment, in the polyamide composition described in the first aspect of the present application, the ratio L / D of L to D is 1.5 to 20, or 1.5 to 15, or 2 to 20.
[0158] For example, in the polyamide composition described in the first aspect of the present application, the ratio L / D of L to D may be 1.5, or 1.6, or 1.7, or 1.8, or 1.9, or 2.0, or 2.2, or 2.4, or 2.6, or 2.8, or 3.0, or 3.2, or 3.4, or 3.6, or 3.8, or 4.0, or 4.2, or 4.4, or 4.6, or 4.8, or 5.0, or 5.2 , or 5.4, or 5.6, or 5.8, or 6.0, or 6.2, or 6.4, or 6.6, or 6.8, or 7.0, or 7.2, or 7.4, or 7.6, or 7.8, or 8.0, or 8.2, or 8.4, or 8.6, or 8.8, or 9.0, or 9.2, or 9.4, or 9.6, or 9.8, or 10.0, or 10.2, or 10.4, or 10.6, or 10.8, or 11.0, or 11.2, or 11.4, or 11.6, or 11.8, or 12.0, or 12.2, or 12.4, or 12.6, or 12.8, or 13.0, or 13.2, or 13.4, or 13.6, or 13.8, or 14.0, or 14.2, or 14.4, or 14.6, or 14.8, or 15.0, or 15.2, or 15 .4, or 15.6, or 15.8, or 16.0, or 16.2, or 16.4, or 16.6, or 16.8, or 17.0, or 17.2, or 17.4, or 17.6, or 17.8, or 18.0, or 18.2, or 18.4, or 18.6, or 18.8, or 19.0, or 19.2, or 19.4, or 19.6, or 19.8, or 20.0.
[0159] The measurement method of L / D can be carried out by methods known to those skilled in the art, for example, the L / D of the glass fiber can be calculated by the SEM image of the cross section. However, it should be understood that those skilled in the art can also use other methods to measure the L / D of the glass fiber.
[0160] In the polyamide composition described in the first aspect of the present application, the content of the flat glass fibers can be adjusted according to the desired properties of the final product.
[0161] According to one embodiment, in the polyamide composition described in the first aspect of the present application, the content of flat glass fibers is 15 to 40 wt %, or 15 to 40 wt %, or 20 to 35 wt %, based on the total weight of the polyamide composition.
[0162] For example, in the polyamide composition described in the first aspect of the present application, the content of flat glass fibers may be 15 weight%, or 16 weight%, or 17 weight%, or 18 weight%, or 19 weight%, or 20 weight%, or 21 weight%, or 22 weight%, or 23 weight%, or 24 weight%, or 25 weight%, or 26 weight%, or 27 weight%, or 28 weight%, or 29 weight%, or 30 weight%, or 31 weight%, or 32 weight%, or 33 weight%, or 34 weight%, or 35 weight%, or 36 weight%, or 37 weight%, or 38 weight%, or 39 weight%, or 40 weight%, based on the total weight of the polyamide composition.
[0163] g) Halogen-free flame retardant
[0164] According to a preferred embodiment, the polyamide composition described in the first aspect of the present application further comprises a halogen-free flame retardant.
[0165] According to one embodiment, the halogen-free flame retardant that can be used in the present application is selected from nitrogen-phosphorus flame retardants or phosphorus-based flame retardants.
[0166] As non-limiting examples of halogen-free flame retardants that can be used in the present application, mention may be made of: triisopropylphenyl phosphate, melamine polyphosphate, triphenyl phosphate, ammonium polyphosphate, etc. However, it should be understood that other halogen-free flame retardants can also be used by those skilled in the art.
[0167] In the polyamide composition described in the first aspect of the present application, the content of the halogen-free flame retardant can be adjusted according to the desired properties of the final product.
[0168] According to one embodiment, in the polyamide composition described in the first aspect of the present application, the content of the halogen-free flame retardant is 15 to 30 weight %, or 15 to 25 weight %, based on the total weight of the polyamide composition.
[0169] For example, in the polyamide composition described in the first aspect of the present application, the content of the halogen-free flame retardant may be 15 weight%, or 16 weight%, or 17 weight%, or 18 weight%, or 19 weight%, or 20 weight%, or 21 weight%, or 22 weight%, or 23 weight%, or 24 weight%, or 25 weight%, or 26 weight%, or 27 weight%, or 28 weight%, or 29 weight%, or 30 weight%, based on the total weight of the polyamide composition.
[0170] h) Antioxidants
[0171] According to a preferred embodiment, the polyamide composition described in the first aspect of the present application may further comprise an antioxidant, wherein the antioxidant comprises a primary antioxidant and a secondary antioxidant.
[0172] According to one embodiment, the primary antioxidant is chosen from copper salts. As non-limiting examples of the primary antioxidant, mention may be made of those available under the references BTN, H318, H3386.
[0173] According to one embodiment, in the polyamide composition described in the first aspect of the present application, the content of the primary antioxidant is 0.01 to 1 weight %, or 0.01 to 0.8 weight %, or 0.01 to 0.6 weight %, or 0.01 to 0.4 weight %, based on the total weight of the polyamide composition.
[0174] For example, in the polyamide composition described in the first aspect of the present application, the content of the primary antioxidant may be 0.01 wt%, or 0.1 wt%, or 0.2 wt%, or 0.3 wt%, or 0.4 wt%, or 0.5 wt%, or 0.6 wt%, or 0.7 wt%, or 0.8 wt%, or 0.9 wt%, or 1.0 wt%, based on the total weight of the polyamide composition.
[0175] According to one embodiment, the secondary antioxidant is selected from hindered phenols and phosphites.
[0176] According to one embodiment, in the polyamide composition described in the first aspect of the present application, the content of the secondary antioxidant is 0.01 to 1 weight %, or 0.01 to 0.8 weight %, or 0.01 to 0.6 weight %, or 0.01 to 0.4 weight %, based on the total weight of the polyamide composition.
[0177] For example, in the polyamide composition described in the first aspect of the present application, the content of the secondary antioxidant may be 0.01 wt%, or 0.1 wt%, or 0.2 wt%, or 0.3 wt%, or 0.4 wt%, or 0.5 wt%, or 0.6 wt%, or 0.7 wt%, or 0.8 wt%, or 0.9 wt%, or 1.0 wt%, based on the total weight of the polyamide composition.
[0178] i) Processing aids
[0179] According to a preferred embodiment, the polyamide composition described in the first aspect of the present application may further comprise a processing aid.
[0180] In the context of the present application, the term "processing aid" means a component which, in addition to the above-mentioned components a) to h), can impart beneficial properties to the final product or make processing easier.
[0181] As non-limiting examples of processing aids that can be used in the present application, OP wax, rice bran wax, CAV102, 816A, pentaerythritol stearate, ethylene bisoleamide, aluminum stearate, calcium montanate, sodium montanate, or a combination thereof can be mentioned. However, those skilled in the art know that the processing aids that can be used in the present application are by no means limited thereto.
[0182] In the polyamide composition described in the first aspect of the present application, the content of the processing aid can be adjusted according to the desired properties of the final product.
[0183] According to one embodiment, in the polyamide composition described in the first aspect of the present application, the content of the processing aid is 0.1 to 2 weight %, or 0.1 to 1.8 weight %, or 0.1 to 1.6 weight %, or 0.1 to 1.4 weight %, or 0.1 to 1.2 weight %, or 0.1 to 1.0 weight %, based on the total weight of the polymer composition.
[0184] For example, in the polyamide composition described in the first aspect of the present application, the content of the processing aid may be: 0.1 wt%, or 0.2 wt%, or 0.3 wt%, or 0.4 wt%, or 0.5 wt%, or 0.6 wt%, or 0.7 wt%, or 0.8 wt%, or 0.9 wt%, or 1.0 wt%, or 1.1 wt%, or 1.2 wt%, or 1.3 wt%, or 1.4 wt%, or 1.5 wt%, or 1.6 wt%, or 1.7 wt%, or 1.8 wt%, or 1.9 wt%, or 2.0 wt%, based on the total weight of the polymer composition.
[0185] The polyamide composition described in the first aspect of the present application is prepared by a method comprising the following steps:
[0186] 1) premixing components a) to d) in a high-speed mixer to obtain a first premix;
[0187] 2) feeding the first premix into a twin-screw extruder, and obtaining a second premix as a masterbatch of wear-resistant additive after the steps of melt extrusion, granulation and drying;
[0188] 3) premixing the wear-resistant additive masterbatch with component e), optionally g), optionally h), and optionally i) in a high-speed mixer to obtain a third premix;
[0189] 4) feeding the third premix and component f) into a twin-screw extruder, and obtaining the polyamide composition after the steps of melt extrusion, granulation and drying, wherein the component f) enters from the side feed port of the twin-screw extruder, and the remaining components enter from the main feed port of the twin-screw extruder.
[0190] It should be understood that the description of the above sub-steps is exemplary rather than limiting. Those skilled in the art may also use other processes to perform the above sub-steps.
[0191] For example, for step 1) and step 3), those skilled in the art know that they can also be carried out by other similar methods, for example, sub-step 1-1 can also be carried out in a planetary mixer, internal mixer, or open mixer.
[0192] In step 2) and step 4), the two screws of the twin-screw extruder can be arranged to rotate in the same direction or in opposite directions. Advantageously, the two screws of the twin-screw extruder can be arranged to rotate in opposite directions.
[0193] The second aspect of the present application relates to a method for preparing the polyamide composition described in the first aspect of the present application, the method comprising:
[0194] 1) Premix the following components a) to d) in a high-speed mixer to obtain a first premix:
[0195] a) aliphatic polyamide resin;
[0196] b) Metal sulfides;
[0197] c) compatibilizer;
[0198] d) coupling agent;
[0199] 2) feeding the first premix into a twin-screw extruder, and obtaining a second premix as a masterbatch of wear-resistant additive after the steps of melt extrusion, granulation and drying;
[0200] 3) Premixing the wear-resistant additive masterbatch with the following components e), optionally g), optionally h), and optionally i) in a high-speed mixer to obtain a third premix:
[0201] e) an amorphous semi-aromatic polyamide resin;
[0202] Optional g) halogen-free flame retardant;
[0203] Optionally h) an antioxidant;
[0204] Optionally i) processing aids;
[0205] 4) feeding the third premix and component f) flat glass fiber into a twin-screw extruder, and obtaining the polyamide composition after a process including melt extrusion, granulation, and drying, wherein the component f) enters from a side feed port of the twin-screw extruder, and the remaining components enter from a main feed port of the twin-screw extruder.
[0206] Components a) to g) and each step described in the second aspect of the present application are the same as those described in the first aspect of the present application.
[0207] The third aspect of the present application relates to the following polyamide composition, which comprises:
[0208] a) aliphatic polyamide resin;
[0209] b) Metal sulfides;
[0210] c) compatibilizer;
[0211] d) coupling agent;
[0212] e) an amorphous semi-aromatic polyamide resin;
[0213] f) flat glass fiber;
[0214] Optional g) halogen-free flame retardant;
[0215] Optionally h) an antioxidant;
[0216] Optionally i) processing aids;
[0217] The polyamide composition has the following characteristics:
[0218] -Tensile strength greater than 150MPa,
[0219] - Flexural strength greater than 200MPa,
[0220] -Notched impact strength greater than 13kJ / m2,
[0221] -Tensile strength retention rate greater than 70%;
[0222] - A coefficient of friction of less than 0.10; and
[0223] -Warp height is less than 0.5mm.
[0224] Example
[0225] The present application is further described below in conjunction with the examples. However, the following examples are merely illustrative and do not limit the present application in any way. The examples and comparative examples of the present application use the materials described in the following Table 1, but are not limited to the materials described in Table 1.
[0226] Table 1 Materials used in Examples and Comparative Examples
[0227]
[0228]
[0229] *The L / D of the flat glass fiber used in the example is 4 / 1, and the L / D is as described above
[0230] The performance test standards and / or methods in the embodiments and comparative examples are as follows:
[0231] (1) Tensile strength: according to ISO 527 method, the specimen size is 170*10*4mm, and the test speed is 5mm / min;
[0232] (2) Notched impact strength: according to ISO 179 / 1eA method, specimen size 80*10*4mm;
[0233] (3) Flexural strength: according to ISO 178 method, specimen size 80*10*4mm, test speed 2mm / min;
[0234] (4) Warping performance: Using a sample bar with a size of 150*100*3 mm, place the sample plate on a table, squeeze the three corners of the plate to warp up the fourth corner. Then measure the warping height of the gap between the surface of the table and the surface of the sample;
[0235] (5) Flame retardant performance: According to UL94 method, the sample size is 125*10*1.6mm;
[0236] (6) Friction coefficient: according to GB 5763 method, sample size 25*25*2mm;
[0237] Embodiment 1:
[0238] Example 1 is carried out by the following steps:
[0239] 1) Weigh each component according to the mass percentage in Table 2.
[0240] 2) Dry the PA6I resin and PA66 resin in a vacuum circulation oven at 120° C. for 6 h, and control the moisture content of the resin to be less than 0.3%.
[0241] 3) The dried PA66 resin, metal sulfide, compatibilizer and coupling agent are uniformly mixed in a high-speed mixer according to the proportions shown in Table 2 to obtain a first premix. The first premix is added from the main feed port of a twin-screw extruder, and is subjected to melt extrusion, granulation and drying in sequence to obtain a second premix as a masterbatch of a wear-resistant additive.
[0242] 4) The wear-resistant additive masterbatch obtained in step 3) is mixed uniformly with the polyamide PA6I resin, halogen-free flame retardant, primary antioxidant, secondary antioxidant and processing aid weighed according to the content of each component in Table 2 in a high-speed mixer to obtain a third premix. The third premix is added from the main feed port of the twin-screw extruder, and the flat glass fiber is added from the side feed port. Each component is subjected to melt extrusion, granulation and drying to obtain a polyamide composition.
[0243] Example 2 Example 1 was repeated except that 5 wt % of molybdenum disulfide was replaced by 5 wt % of bismuth sulfide.
[0244] Example 3 Example 1 was repeated, except that the content of molybdenum disulfide was increased to 10 wt %, based on the total weight of the polyamide composition; and the content of PA6I was correspondingly reduced to 15 wt %, based on the total weight of the polyamide composition.
[0245] Comparative Example 1 Example 1 was repeated, except that no PA6I was added and the content of PA66 was increased to 39.5% by weight, relative to the total weight of the polyamide composition.
[0246] Comparative Example 2 Example 1 was repeated except that no metal disulfide was added and the content of PA6I was increased to 25 wt%.
[0247] Comparative Example 3 Example 1 was repeated except that no compatibilizer was added and the content of PA6I was increased to 23 wt %.
[0248] Comparative Example 4 Example 1 was repeated except that no coupling agent was added and the content of PA6I was increased to 21.5 wt %.
[0249] Comparative Example 5 : The polyamide composition is prepared by a one-step method, and the specific preparation process is as follows:
[0250] 1) Weigh each component according to the mass percentage in Table 2.
[0251] 2) Dry the PA6I resin and PA66 resin in a vacuum circulation oven at 120° C. for 6 h, and control the moisture content of the resin to be less than 0.3%.
[0252] 3) Mix all components except flat glass fiber in a high-speed mixer.
[0253] 4) The premix obtained in step 3) is added from the main feed port of the twin-screw extruder, and the flat glass fiber is added from the side feed port. Each component is subjected to melt extrusion, granulation, and drying to obtain a polyamide composition.
[0254] Comparative Example 6 Example 1 was repeated, except that no halogen-free flame retardant was added and the content of PA6I was increased to 40 wt %, relative to the total weight of the polyamide composition.
[0255] Comparative Example 7Example 1 was repeated, except that no primary antioxidant was added and the content of PA66 was increased to 19.8 wt %, relative to the total weight of the polyamide composition.
[0256] Comparative Example 8 Example 1 was repeated, except that: no primary antioxidant was added, the content of PA66 was increased to 19.8 wt %, relative to the total weight of the polyamide composition; and round glass fibers were used instead of flat glass fibers.
[0257] The performance test results of the polyamide compositions obtained in various examples and comparative examples are shown in Table 2.
[0258] Table 2
[0259]
[0260]
[0261] * Conventional round glass fibers were used in Comparative Example 8, and flat glass fibers were used in the remaining comparative examples and all the examples.
[0262] It can be seen from the results shown in the examples and comparative examples that the present application obtains a polyamide composition having good mechanical properties, low friction coefficient and low warpage performance by using a two-step preparation process and specific components.
[0263] Comparison between Example 1 and Comparative Example 5 shows that the preparation process of the polyamide composition of the present application has a significant effect on the performance of the final polyamide composition. The difference between Example 1 and Comparative Example 5 is that Example 1 adopts the two-step method described in the present application to prepare the polyamide composition, while Comparative Example 5 adopts the one-step method to prepare the polyamide composition. The results in Table 2 are limited. Under the condition that all components are the same, the use of the two-step method can significantly improve the tensile strength (from 143MPa to 181MPa) and notched impact strength (from 9.8kJ / m2 to 181MPa) of the polyamide composition relative to the one-step method without sacrificing the high bending strength, high tensile strength retention rate, low friction coefficient and low warpage height of the polyamide composition. 2 Increased to 16.4 kJ / m 2 ).
[0264] Comparison between Example 1 and Examples 3 and 4 shows that the joint use of a compatibilizer and a coupling agent brings about a significant improvement in the tensile strength and notched impact strength of the polyamide composition, and this improvement does not come at the expense of other properties of the polyamide composition (including flexural strength, tensile strength retention, flame retardancy, friction coefficient and low warpage).
[0265] Comparison of Example 1 and Comparative Example 1 shows that the use of both the aliphatic polyamide resin and the amorphous semi-aromatic polyamide resin significantly reduces the warpage height of the polyamide composition (from 2.1 mm to 0.2 mm).
[0266] In addition, the cross-sectional shape of the glass fiber also has a significant effect on the performance of the polyamide composition. The results of Comparative Example 8 show that the use of round glass fibers will significantly increase the warpage of the polyamide composition.
[0267] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A polyamide composition, comprising: a) aliphatic polyamide resin; b) Metal sulfides; c) compatibilizer; d) coupling agent; e) an amorphous semi-aromatic polyamide resin; f) Flat glass fiber; Optionally g) a halogen-free flame retardant; Optionally h) an antioxidant; Optional i) processing aids; The polyamide composition is prepared by the following method: 1) premixing components a) to d) in a high-speed mixer to obtain a first premix; 2) feeding the first premix into a twin-screw extruder, and obtaining a second premix as a masterbatch of wear-resistant additive after the steps of melt extrusion, granulation and drying; 3) premixing the wear-resistant additive masterbatch with component e), optionally g), optionally h), and optionally i) in a high-speed mixer to obtain a third premix, 4) feeding the third premix and component f) flat glass fiber into a twin-screw extruder, and obtaining the polyamide composition after a process including melt extrusion, granulation, and drying, wherein the component f) enters from a side feed port of the twin-screw extruder, and the remaining components enter from a main feed port of the twin-screw extruder.
2. The polyamide composition according to claim 1, wherein (1) The aliphatic polyamide resin is obtained by the condensation of: -C x Aliphatic lactams; -C y aliphatic amino acids; or -C a Aliphatic diacids and C b Aliphatic diamines. Preferably: The C x The aliphatic lactam is selected from C4 to C 12 Aliphatic lactam, or C4 to C 10 Aliphatic lactam, or C4 to C8 aliphatic lactam; and / or The C y The aliphatic amino acids are selected from C4 to C 12 Aliphatic amino acids, or C4 to C 10 aliphatic amino acids, or C4 to C8 aliphatic amino acids; and / or The C a The aliphatic diacid is selected from C4 to C 12 Aliphatic diacids, or C4 to C 10 an aliphatic diacid, or a C4 to C8 aliphatic diacid; and / or The C b The aliphatic diamine is selected from C4 to C 12 Aliphatic diamine, or C4 to C 10 Aliphatic diamine, or C4 to C8 aliphatic diamine; and / or (2) The content of the aliphatic polyamide resin is 10 to 40 wt%, or 10 to 35 wt%, or 10 to 30 wt%, based on the total weight of the polyamide composition.
3. The polyamide composition of claim 1, wherein the metal sulfide has one or more of the following characteristics: (1) The metal in the metal sulfide is selected from transition metals, Group IV metals, and Group V metals; and / or (2) The metal in the metal sulfide is selected from tin, bismuth, iron, cobalt, nickel, copper, zinc, molybdenum, and tungsten; and / or (3) The content of the metal sulfide is 5 to 20 wt%, or 5 to 18 wt%, or 5 to 16 wt%, or 5 to 14 wt%, or 5 to 12 wt%, based on the total weight of the polyamide composition.
4. The polyamide composition according to claim 1, wherein the compatibilizer is selected from copolymers formed by hydrophilic units and hydrophobic units, preferably selected from graft copolymers formed by hydrophilic compounds and hydrophobic polymers; Preferably, the compatibilizer has one or more of the following characteristics: (1) The hydrophilic unit is a unit derived from acrylic acid, acrylamide, vinyl alcohol, vinyl alcohol ester, vinyl sulfonic acid, p-vinyl benzoic acid, or maleic anhydride; and / or (2) The hydrophobic unit is a unit derived from α-olefin, diolefin, styrene or acrylonitrile; and / or (3) the hydrophilic compound is derived from one or more of acrylic acid, acrylamide, vinyl alcohol, vinyl alcohol ester, vinyl sulfonic acid, p-vinyl benzoic acid, or maleic anhydride; and / or (4) The hydrophobic polymer is formed from one or more of α-olefins, dienes, styrene, and acrylonitrile; and / or (5) The compatibilizer is selected from one or more of PP-g-MAH, PE-g-MAH, EVA, and ABS-g-MAH; and / or (6) The content of the compatibilizer is 1 to 5 wt %, or 1 to 4.5 wt %, or 1 to 4 wt %, or 1 to 3.5 wt %, based on the total weight of the polyamide composition.
5. The polyamide composition of claim 1, wherein the coupling agent has one or more of the following characteristics: (1) The coupling agent is selected from: one or more of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent; and / or (2) The content of the coupling agent is 1 to 3 wt %, or 1 to 2.5 wt %, or 1 to 2 wt %, based on the total weight of the polyamide composition.
6. The polyamide composition of claim 1, wherein the amorphous semi-aromatic polyamide resin has one or more of the following characteristics: (1) the amorphous semi-aromatic polyamide resin is selected from the group consisting of PA6I, 11 / B10, 12 / B10, 11 / P10, 12 / P10, 11 / BI / BT, 12 / BI / BT, 11 / PI / BT, 12 / PI / BT, 11 / PI / PT, 12 / PI / PT, 11 / BI, 12 / BI, 11 / PI and 12 / PI; and / or (2) The content of the amorphous semi-aromatic polyamide resin is 10 to 40 wt%, or 10 to 35 wt%, or 10 to 30 wt%, or 10 to 25 wt%, based on the total weight of the polyamide composition.
7. The polyamide composition of claim 1, wherein the flat glass fibers have one or more of the following characteristics: (1) The flat glass fiber has a ratio L / D of a longer dimension L to a shorter dimension D in a flat glass fiber cross section perpendicular to the length direction of the flat glass fiber of 1.5 to 20, or 1.5 to 15, or 2 to 20; and / or (2) The content of the flat glass fiber is 15 to 40 wt%, or 15 to 40 wt%, or 20 to 35 wt%, based on the total weight of the polyamide composition.
8. The polyamide composition of claim 1, wherein the polyamide composition further comprises one or more of the following components g), h) and i): g) Halogen-free flame retardant; Preferably, the halogen-free flame retardant has one or more of the following characteristics: (1) the content of the halogen-free flame retardant is 15 to 30 wt %, or 15 to 25 wt %, based on the total weight of the polyamide composition; and / or (2) The halogen-free flame retardant is selected from nitrogen-phosphorus flame retardants or phosphorus-based flame retardants; h) antioxidants; Preferably, the antioxidant comprises a primary antioxidant and a secondary antioxidant; Preferably, the antioxidant has one or more of the following characteristics: (1) The primary antioxidant is selected from copper salts; and / or (2) The primary antioxidant is selected from BTN, H318, H3386; and / or (3) the content of the primary antioxidant is 0.01 to 1 wt %, or 0.01 to 0.8 wt %, or 0.01 to 0.6 wt %, or 0.01 to 0.4 wt %, based on the total weight of the polyamide composition; and / or (4) The secondary antioxidant is selected from: hindered phenols, phosphites; and / or (5) the content of the secondary antioxidant is 0.01 to 1 wt %, or 0.01 to 0.8 wt %, or 0.01 to 0.6 wt %, or 0.01 to 0.4 wt %, based on the total weight of the polyamide composition; i) Processing aids Preferably, the processing aid has one or more of the following characteristics: (1) the content of the processing aid is 0.1 to 2 weight %, or 0.1 to 1.8 weight %, or 0.1 to 1.6 weight %, or 0.1 to 1.4 weight %, or 0.1 to 1.2 weight %, or 0.1 to 1.0 weight %, based on the total weight of the polymer composition; and / or (2) The processing aid is selected from OP wax, rice bran wax, CAV102, 816A, pentaerythritol stearate, ethylene bisoleamide, aluminum stearate, calcium montanate, sodium montanate, or a combination thereof.
9. A method for preparing a polyamide composition according to any one of claims 1 to 8, the method comprising: 1) Premix the following components a) to d) in a high-speed mixer to obtain a first premix: a) aliphatic polyamide resin; b) Metal sulfides; c) compatibilizer; d) coupling agent; 2) feeding the first premix into a twin-screw extruder, and obtaining a second premix as a masterbatch of wear-resistant additive after the steps of melt extrusion, granulation and drying; 3) Premixing the anti-wear additive masterbatch with the following components e), optionally g), optionally h), and optionally i) in a high-speed mixer to obtain a third premix: e) an amorphous semi-aromatic polyamide resin; Optional g) halogen-free flame retardant; Optionally h) an antioxidant; Optionally i) processing aids; 4) feeding the third premix and component f) flat glass fiber into a twin-screw extruder, and obtaining the polyamide composition after a process including melt extrusion, granulation, and drying, wherein the component f) enters from a side feed port of the twin-screw extruder, and the remaining components enter from a main feed port of the twin-screw extruder.
10. A polyamide composition comprising: a) aliphatic polyamide resin; b) Metal sulfides; c) compatibilizer; d) coupling agent; e) an amorphous semi-aromatic polyamide resin; f) flat glass fiber; Optional g) halogen-free flame retardant; Optionally h) an antioxidant; Optionally i) processing aids; The polyamide composition has the following characteristics: -Tensile strength greater than 150MPa, - Flexural strength greater than 200MPa, -Notched impact strength greater than 13kJ / m 2 , - tensile strength retention greater than 70%; - friction coefficient less than 0.10; and -Warp height is less than 0.5mm.